Flavonoids as Adjuvant in Psoralen-based Phytochemotherapy in the Management of Vitiligo/Leukoderma - Sureshkumar, Dr. R. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: Vitiligo is a skin disorder due to the decrease in the concentration of melanin pigment on our skin. In this work, we propose to utilize the flavonoids to augment the phytochemotherapy with vitiligo. Materials and Methods: Hesperidin is used as a natural ingredient in this formulation. This work is to develop a novel drug combination loaded lipid-based nanoemulsion gel. This is a novel strategy to reduce the duration of ultraviolet (UV) radiation in psoralen plus UVA therapy. Induction of the vitiligo in C57BL/6 mice using monobenzone and treating the induced animal with the drug-loaded nanoemulsion gel. Results and Discussion: Nanoemulsion gel is prepared and characterization studies were carried out. In vivo studies were carried out in the animals immediately after the induction of vitiligo. It is proved that the treatment is supporting with the repigmentation. Conclusion: For this study, it is proven that the use of the hesperidin as a flavonoid with trimethylpsoralen combination acts as an effective phytochemotherapy agent for psoralen treatment.